G217(P) Neonatal chylothorax: a pathway based on a literature review and ten years experience in a tertiary neonatal referral centre. (May 2019) - White, MK; Bhat, R; Greenough, A
Abstract : Aim: Neonatal chylothorax is a rare condition with an incidence of 1 in 5775 [1] to 24000 [2] and has a high mortality rate of up to 64% [2]. Our aim was to create a pathway for the diagnosis and management of neonatal chylothorax based on experience in a tertiary neonatal referral centre and a review of the literature. Methods: A 10 year retrospective audit of all neonates with a chylothorax was performed. A search of electronic databases including keywords such as neonates and chylothorax identified all relevant papers. A pathway was created based on the audit results and the literature review. Results: Over 10 years, six patients were diagnosed with a chylothorax, two were congenital and four iatrogenic post thoracic surgery or instrumentation. Patients were ventilated for a median of 30 days with a maximum daily pleural fluid output of 218 mls/kg/day. All patients received medium-chain triglyceride (MCT) feeds which five tolerated with no increase in pleural output. Octreotide was used in three patients with no reduction in pleural fluid output. Two neonates needed surgical intervention: one had thoracic duct ligation and the other bilateral pleurodesis. The median length of stay was 68 days and five neonates survived. Two patients with follow up had normal growth and development at one year of age. The literature review revealed that supportive care and MCT feeds were the mainstay of conservative management of neonatal chylothorax. Somatostatin and more recently octreotide, a somatostatin analogue, have been used with variable dosing regimens, length of treatment and outcomes. Surgical intervention including thoracic duct ligation or pleurodesis is used for those cases not responding to conservative or medical management. A pathway was then created highlighting which cohort of patients are at risk of neonatal chylothorax, how to diagnose it and a flow chart for the management of neonatal chylothorax. Conclusion: Neonatal chylothorax is a rare condition and there is no standardised management, hence we have created an evidence and experience based pathway to improve diagnosis and management. References: Downie L, et al. J Paediatr Child Health 2014;50:234–8. Bialkowski A, et al. Arch Dis Child Fetal Neonatal Ed 2015;100:F169–72.